Individual differences and motives for the acceptance of cognitive enhancement: A mixed-methods investigation - Sandra Grinschgl; Larissa Kohlmeier; Aljoscha C. Neubauer (PLoS ONE, 2026)
Despite a long history of human efforts to enhance cognitive abilities such as attention, memory, and intelligence, the proliferation of (new) technological and medical methods—including brain stimulation, pharmaceutical interventions, and gamified brain training—has renewed scientific and public interest in cognitive enhancement, even as evidence for their effectiveness in improving broader cognitive abilities remains inconsistent. Understanding who would be willing to enhance their cognitive abilities and why is crucial as these cognitive enhancement methods become more popular and accessible in society. Thus, in two preregistered lab studies, we investigated individuals’ acceptance (i.e., hypothetical willingness to make use) of various cognitive enhancement methods, tested predictors thereof, and explored individuals’ motives to utilize cognitive enhancement methods or be reluctant to do so. In Study 1 ( N = 203), we found considerably higher acceptance for more active (i.e., more involved) than passive cognitive enhancement methods. Lower age, greater interest in science fiction, and stronger investigative interests (partially) predicted participants’ acceptance of cognitive enhancement methods, while personality traits, self-assessed and measured intelligence did not. In Study 2 ( N = 197), we aimed to (conceptually) replicate key findings from Study 1, and in addition qualitatively assess the motives for the acceptance and rejection of cognitive enhancement methods. Our findings confirmed the higher acceptance of active than passive cognitive enhancement methods. Additionally, we found that greater interest in science fiction consistently predicted participants’ acceptance of cognitive enhancement, while personality traits and (self-assessed) intelligence did not show consistent associations. Critically, these quantitative effects were rather small. Qualitative analyses additionally provided exploratory insights into the motives for accepting or rejecting active and passive cognitive enhancement methods. Across these two studies, acceptance of cognitive enhancement seems to be more closely linked to specific interests than to personality traits or (self-assessed) abilities. We emphasize the importance of studying situational factors, such as person-environment fit, to better understand the willingness to make use of cognitive enhancement.